Control Strategies for Solution‐Processed ZTO‐Based Thin‐Film Transistors Tailored Toward Volatile Organic Compound Detection - Lauren R. Miller; Alejandro Galán‐González; Ben Nicholson; Leon Bowen; Guillaume Monier; Robert J. Borthwick; Freddie White; Mana Saeed; Richard L. Thompson; Christine Robert‐Goumet; Del Atkinson; Dagou A. Zeze; et al. (Advanced Electronic Materials)
Abstract A breakthrough in the fabrication of amorphous Zn‐Sn‐O (ZTO)‐based thin‐film transistors (TFTs) is presented for volatile organic compound (VOC) detection. The incorporation of highly abundant materials offers substantial economic and environmental benefits. However, analyses for the design of a multilayer channel are still limited. This work demonstrates that the chemical environment influences ZTO‐based TFTs' carrier transport properties and can be tailored for detecting specific VOCs, ensuring high specificity in diagnosing life‐threatening conditions through simple breath analysis. A low‐cost, high‐throughput, fully solution‐processed ZTO and ZnO multilayering strategy is adopted. The in‐depth compositional and morphological analyses reveal that low surface roughness, excellent Zn and Sn intermixing, high oxygen vacancy (31.2%), and M‐OH bonding (11.4%) contents may account for the outstanding electrical and sensing performance of ZTO‐ZTO TFTs. Notably, these TFTs achieve near‐zero threshold voltage (2.20 V), excellent switching properties (107), and high mobility (10 cm2V−1s−1). This results in high responsivity to alcohol vapors at low‐voltage operation with peak responsivity for methanol (R = 1.08 × 106) over two orders of magnitude greater than acetone. When miniaturized, these devices serve as easy‐to‐operate sensors, capable of detecting VOCs with high specificity in ambient conditions.